NEW AYAKAGITMA-2 NEOLITHIC SITE OF SOUTH-WEST KYZYLKUM - Saifullayev Bakhtiyor Kurbanovich; Elmuratov Bakhodir Abdugapparovich (Western European Studies, 2024)
In this article, The Kyzylkum desert was a vast valley 5-6 thousand years ago, the "country of a thousand lakes", where the ancestors of mankind lived very densely. During an archaeological field search survey conducted in the area of Gijduvan district (Ayakagitma suburb) of Bukhara region, an archaeological investigation was carried out. The results from these studies are equivalent to scientifically proving that the caltaminorites were not only hunters and fishermen, but also skilled breeders who domesticated camels, cattle and sheepgoats, giving a chronological sans of this culture for another 700 thousand years, that is, the land.in the 1st century BC. It made it Ancient until the 6300 thousand years.A new Ayakagitma-2 Neolithic site dating to the Neolithic period was found on the Northern Board of the Ayakagitma swamp. Finds excavated from the monument, where the eastern side of the space adjoins a high hill, and the ravine on the southern side washed away much of it, revealed 370 stone artifacts, a small number of animal bones, and ocher remains. Further laboratoryChamber studies clarify the issue of cultural-periodic characteristics of the acquired items.
Keywords: Neolithic; flake